1994
DOI: 10.1063/1.357052
|View full text |Cite
|
Sign up to set email alerts
|

Origin of n-type conductivity of low-temperature grown InP

Abstract: It is shown with correlated magnetic resonance and electrical measurements that the PIn antisite is the prevailing defect in InP grown by molecular-beam epitaxy at low temperature. The first ionization level of the PIn antisite is resonant with the conduction band, which makes the material n-type conducting due to autoionization of the PIn antisite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…P In antisites and V P vacancies are dominant donors in InP and InP 1−x Bi x . Chen et al found a level of 0.23 eV below conduction band minimum (CBM) and a level 0.12 eV above CBM hypothetically corresponding to P In level and V P level [18], respectively, in which the P In level does not accord with our experimental results as shown in Section 3.3. V P and P In concentration dominates the electron concentration at low Bi content (x < 1.83%) and high Bi content (x >1.83 %), respectively.…”
Section: Electrical and Transport Propertiescontrasting
confidence: 77%
“…P In antisites and V P vacancies are dominant donors in InP and InP 1−x Bi x . Chen et al found a level of 0.23 eV below conduction band minimum (CBM) and a level 0.12 eV above CBM hypothetically corresponding to P In level and V P level [18], respectively, in which the P In level does not accord with our experimental results as shown in Section 3.3. V P and P In concentration dominates the electron concentration at low Bi content (x < 1.83%) and high Bi content (x >1.83 %), respectively.…”
Section: Electrical and Transport Propertiescontrasting
confidence: 77%
“…In the reduced atmosphere, Mohapatra and Kröger pointed out that a Ti ion is in the charge state of ϩ3 at the Al 3ϩ site, and induces a deep impurity level occupied by one electron within the band gap ͑4.25 eV from the conduction band minimum͒. [7][8][9] The objective of this study is, therefore, to verify a possibility of Ti 3ϩ association or clustering in Al 2 O 3 using first-principles calculations. 5 When dilute Ti 3ϩ solutes are dispersed through the Al 2 O 3 lattice ͑namely, in the isolated state of Ti 3ϩ ions͒, therefore, significant additional energy is required for excitation of an electron at the impurity level to the conduction band.…”
Section: Y Ikuharamentioning
confidence: 97%
“…9 In InP, the presence of these defects has a different character, creating n-type free carriers. 8 In this article, we have investigated the possibility to achieve high resistivity and ultrashort photoexcited carrier lifetimes in As ϩ -and P ϩ -implanted InP.…”
Section: Introductionmentioning
confidence: 99%